2022
DOI: 10.1038/s41598-022-09810-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity for agromorphological traits, phytochemical profile, and antioxidant activity in Moroccan sorghum ecotypes

Abstract: Sorghum, the fifth most important cereal crop, is a well-adapted cereal to arid/semi-arid regions. Sorghum is known for multiple end-uses as food, feed, fuel, forage, and as source of bioactive compounds that could be used for medical applications. Although the great improvement in the process of sorghum breeding, the average yield of this crop is still very low. Therefore, exploring the genetic diversity in sorghum accessions is a critical step for improving this crop. The main objective of the current work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…In line with our findings, the phenotypic correlation studies in cucumber showed that fruit yield plant −1 exhibited a positive and significant correlation with fruits plant −1 , fruit length, fruit weight, fruit width, branches plant −1 and plant height 10 . Many researchers reported in earlier findings that leaves are important trait for plants photosynthetic performance, architecture and yield potential, thus, a good trait to be targeted for breeding programme for development and selection of targeted trait variety 12 . The characters like showed high positive correlation both in phenotypic as well as genotypic level, which indicating that there was simultaneous selection for these characters might bring an improvement in fruit yield of plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our findings, the phenotypic correlation studies in cucumber showed that fruit yield plant −1 exhibited a positive and significant correlation with fruits plant −1 , fruit length, fruit weight, fruit width, branches plant −1 and plant height 10 . Many researchers reported in earlier findings that leaves are important trait for plants photosynthetic performance, architecture and yield potential, thus, a good trait to be targeted for breeding programme for development and selection of targeted trait variety 12 . The characters like showed high positive correlation both in phenotypic as well as genotypic level, which indicating that there was simultaneous selection for these characters might bring an improvement in fruit yield of plant.…”
Section: Resultsmentioning
confidence: 99%
“…Variability for morphological and qualitative traits including antioxidants among C. grandis germplasm are frequently used in breeding programs for developing cultivars with consumer liking is a prerequisite to efficiently manage and utilize germplasm. The PCA and clustering analysis of morphological characterization are relatively inexpensive and easy to carry out for conservation of genetic resources, identification of characters amenable to genetic improvement and selection of high yielding genotypes 12 . The success of good breeding and selection of promising germplasm depends on the genetic variability present in the germplasm population and the variation in the population helps to identify suitable germplasm for vital traits and conserve and classify genetic variation in the plant germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…To produce crops with a greater amount of desirable compounds, several strategies can be followed. The first is to select species, genotypes, or cultivars that contain a genetically determined higher level of phytochemicals (Bouargalne et al, 2022;Zhan et al, 2022). The second is to manipulate the growth factors and environmental conditions for plant cultivation (Trejo-Téllez et al, 2019;Šamec et al, 2021).…”
Section: Functions Of Gsls In Plantsmentioning
confidence: 99%
“…Due to climate change with more prolonged drought periods, the decrease in water supply, and the increasing world population, this drought-resistant crop, like other available local feed alternatives 10 , could quickly become crucial and see its global use increase. Previous studies emphasized the agro-morphological and genetical diversity of some Moroccan ecotypes 7 , 11 , 12 . However, no studies assessed the nutritive value as feed on these ecotypes.…”
Section: Introductionmentioning
confidence: 99%